2015
DOI: 10.5750/ejpch.v3i3.985
|View full text |Cite
|
Sign up to set email alerts
|

Measuring family-centred care: working with children and their parents in a Turkish hospital

Abstract: Rationale, aims and objectives: Family-centred care is the model of care in most children’s hospitals, but is difficult to measure. This study examined health professionals’ attitudes to working with children and with parents in a Turkish hospital. It builds on previous studies, using the same questionnaire, to test a component of family-centred care. Method: The “Working with Families” questionnaire contains scores for working with children and parents and demographic questions. Nurses, doctors and allied hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
2
14
1
2
Order By: Relevance
“…Family choice and action Responses in this cluster of PIs indicate that the respondents did not always use practices that encourage family participation and decisionmaking in the illness experience. In a study in Turkey, Shields et al [5] found that the family of patients in the ED wanted to partner with healthcare professionals, which suggests that participatory practices should be considered when planning FCC. Just over half of the respondents in the current study indicated that they partnered with family members to identify and subsequently address their desires.…”
Section: Participatory Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Family choice and action Responses in this cluster of PIs indicate that the respondents did not always use practices that encourage family participation and decisionmaking in the illness experience. In a study in Turkey, Shields et al [5] found that the family of patients in the ED wanted to partner with healthcare professionals, which suggests that participatory practices should be considered when planning FCC. Just over half of the respondents in the current study indicated that they partnered with family members to identify and subsequently address their desires.…”
Section: Participatory Practicesmentioning
confidence: 99%
“…Other challenges include the limited understanding of FCC principles by healthcare professionals and communication difficulties. [4,5] In South Africa (SA), trauma accounts for the greatest number of unnatural deaths and disabilities in emergency departments (EDs). [6] The initial management of a critical illness occurs in the ED, which results in emergency care and critical care being considered as one in the continuum of acute care.…”
mentioning
confidence: 99%
“…46 Bu konuda sağlık personelinin, çocuklar ve ebeveynler ile birlikte çalışmayı nasıl algıladıklarını ölçen çeşitli çalışmalar yapılmıştır. 9,22,24,46,47 Ülkemizde bir üniversite hastanesinin pediatri kliniklerinde, 2014 yılında yapılan aile merkezli bakıma ilişkin uluslararası karşılaştırmalı bir çalışmada; hemşire, hekim ve yardımcı sağlık personelinin, çocuk ve ebeveynler ile birlikte çalışmayı nasıl algıladıkları incelenmiştir. 9,47 Türkiye'de 11 klinikte toplam 85 hemşire, 75 hekim ve 45 yardımcı sağlık personeli üzerinde yapılan çalışmada, sağlık personelinin çocuklarla birlikte çalışmaya ilişkin puan ortalamaları (4,24), ebeveynlere göre (2,27) daha yüksek bulunmuştur.…”
Section: Ai̇le Merkezli̇ Bakimin Etki̇nli̇ği̇unclassified
“…The concept of FCS emerged from Western countries, and there are several reports investigating the implementation of FCS in non‐Western societies (Al‐Motlaq, Abuidhail, Salameh, & Awwad, ; Al‐Motlaq & Shields, ; Himuro, Miyagishima, Kozuka, Tsutsumi, & Mori, ; Kang, Palisano, Simeonsson, & Hwang, ; Linda Shields, Çavuşoğlu, Pars, & Mamun, ; Tang, Chong, Goh, Chan, & Choo, ). In Turkey, neither the Ministry of Health nor state and private hospitals have developed health policies or institutional regulations on family‐centred practices yet (Feeg et al, ).…”
Section: Introductionmentioning
confidence: 99%